Pengaruh Pembelajaran CTL Dengan Kemampuan Awal Matematika Terhadap Pemahaman Konsep Matematis Siswa Sekolah Dasar - Akhiriani Rambe; Kms. Muhammad Amin Fauzi; Ishaq Nuriadin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study was to determine whether there was an effect of CTL learning and conventional learning with early mathematics abilities on the understanding of the fourth grade students of SD Negeri 117471 Sibargot. The research method used was an experiment using pre-test and post-test control group design. Hypothesis testing in this study used a two-way analysis of variance (ANOVA) test with a significance level of α = 0.05. The results of this study indicate that the sig. for CTL (MP₁) and Conventional Learning (MP₂) is the result of tcount -2.911> ttable 2.002, so it can be concluded that H1 is accepted, which means that there is a significant influence of the learning model on understanding mathematical concepts; sig value. for Mathematical Initial Ability (KAM) with the result of tcount -6.434> ttable 2.002 shows that the mean of the first group, namely high initial ability (KAMt) is higher than the second group, namely low initial ability (KAMr), so it can be concluded that H2 is accepted, which means that there is an influence. significant initial ability to understand mathematical concepts; sig value. for the effect of the Learning Method and KAM simultaneously on understanding mathematical concepts with the results of the value of Fcount 24.933> Ftable 3.16. So it can be concluded that H3 is accepted, which means that there is an effect of learning methods and Early Ability simultaneously on understanding mathematical concepts.